Chlorogenic Acid Protects Cell Death in the Cerebellum through Anti-Apoptotic Protein Bcl2 in Transient Global Ischemia Cases - Ery Hermawati; Mitra Handini; Muhammad In'am Ilmiawan; Mahyarudin Mahyarudin (Cell and BioPharmaceutical Institute, 2024)
Background: Cerebellum is one of the vital components of the brain that will be affected by ischemia-reperfusion (IR) injury. IR injury will increase free radicals, which in turn can trigger apoptosis and cell death. Therefore, this study was conducted to examine the effect of chlorogenic acid administration on apoptosis and the number of cells in the cerebellum of rats with global ischemic transients. Materials and methods: Wistar rats were divided into five groups: sham-operated (C1), IR (C2), IR + 15 mg/kgBW chlorogenic acid (T1), IR + 30 mg/kgBW chlorogenic acid (T2), and IR + 60 mg/kgBW chlorogenic acid (T3). C2, T1, T2, and T3 groups received bilateral common carotid occlusion (BCCO) surgery to induce IR injury. Thirty minutes after BCCO surgery, T1, T2, and T3 rats were administered chlorogenic acid in various doses intraperitoneally. RNA extraction and real-time polymerase chain reaction (PCR) measurements were then performed on NeuN, Bcl2, Bax, caspase 3, as well as on GAPDH as housekeeping genes. Results: There were significant differences in NeuN expressions between groups, with the highest expression shown in C1 followed by T3. Bcl2 expressions were also significantly different between groups, and rats in C1 and T3 showed to be significantly higher compared to C2, while T1 was significantly lower than C1. However, Bax and caspase 3 expressions showed no significant differences. Conclusion: Chlorogenic acid in 60 mg/kgBW dose increases NeuN expression and Bcl2 mRNA expression after transient global ischemia. These increases might correlate with the heightened level of protection against apoptosis in the cerebellum, hence showing its potential in protecting neuron cells. Keywords: transient global ischemia, chlorogenic acid, cerebellum, apoptosis